Antarctic ice rises and rumples: their properties and significance for ice-sheet dynamics and evolution - Matsuoka, Kenichi; Hindmarsh, Richard C A; Moholdt, Geir; Bentley, Michael J; Pritchard, Hamish D; Brown, Joel; Conway, Howard; Drews, Reinhard; Durand, Gaël; Goldberg, Daniel; Hattermann, Tore; Kingslake, Jonathan; et al. (Earth-Science Reviews, 2015)
Locally grounded features in ice shelves, called ice rises and rumples, play a key role buttressing discharge from the Antarctic Ice Sheet and regulating its contribution to sea level. Ice rises typically rise several hundreds of meters above the surrounding ice shelf; shelf flow is diverted around them. On the other hand, shelf ice flows across ice rumples, which typically rise only a few tens of meters above the ice shelf. Ice rises contain rich histories of deglaciation and climate that extend back over timescales ranging from a few millennia to beyond the last glacial maximum. Numerical model results have shown that the buttressing effects of ice rises and rumples are significant, but details of processes and how they evolve remain poorly understood. Fundamental information about the conditions and processes that cause transitions between floating ice shelves, ice rises and ice rumples is needed in order to assess their impact on ice-sheet behavior. Targeted high-resolution observational data are needed to evaluate and improve prognostic numerical models and parameterizations of the effects of small-scale pinning points on grounding-zone dynamics.
Keywords: Antarktis; Sørishavet; glasiologi; havis

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Article Number: 414
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi